Mental training for young athlete: A case of study of NLP practice - Wissal Boughattas; Manel Ben Salha; Najwa Moella (Elsevier, 2022)
Aims: To examine the effect of neurolinguistic programming (NlP) and its processes on psychosomatic skills (cognitive anxiety and somatic anxiety), basic skills (self-confidence and physical self-esteem), and athletic performance of young Tunisian swimmers. Materials: For this study, we use the NLP techniques for mental preparation. Semi-structured interviews were used with the tow psychological scale to measure mental skills. Sportive performance were measured before and after intervention. Methods: This study is quantitative research with the pretest-posttest design. Six adolescent swimmers (3 girls and 3 boys); M age ​= ​15.8 years participated for six months in a mental preparation program based on neurolinguistic programming techniques. Result: The results of this work showed better management of anxiety during the competition, as well as an improvement in self-confidence and physical self-esteem. We also note an important amelioration in the athlete's performance (from 0.77% to 2.5%). Conclusion: In view of the positive results obtained during this study, especially in terms of anxiety management and performance improvement, we suggest more exploration of the effect of different NLP techniques in sport. We also recommend more frequent use of NLP with athletes.